The Dynamics of Nutrition Program Implementation in Ethiopia: Facilitators and Constraints at National and Sub-National Level. - Tessema, Masresha. (Tufts University. Tisch Library., 2016)
This reports details a study that assessed the facilitators and constraints to adopting the National Nutrition Program at the national and sub national level. Key issues were identified including leadership, coordination, awareness, capacity and budget. A series of recommendations derived from the study data are included.; Nutrition School: Technical Reports.; Keywords: Ethiopian Public Health Institute, Federal Ministry of Health, Save the Children, National Nutrition Program.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy